The Royal Navy and the German threat 1901-1914 admiralty plans to protect British trade in a war against Germany - Seligmann, Matthew S. 1967- (Oxford University Press, 2012)
This is an account of the efforts made by the Royal Navy to prepare for war with Germany more than a decade before 1914. Seligmann demonstrates that from being unready for an assault on British seaborne trade, the Royal Navy had given a great deal of thought to its protection
Includes bibliographical references and index
Keywords: Great Britain / Royal Navy / History / 20th century; Germany / Kriegsmarine / History / 20th century; Geschichte 1900-2000; Geschichte 1901-1914; Geschichte; Sea-power / Great Britain / History / 20th century; Sea-power / Germany / History / 20th century; Marinepolitik; Deutschland; Großbritannien; Great Britain / History, Naval / 20th century; Germany / History, Naval / 20th century